Association of Total Calcium With Serum Uric Acid Levels Among United States Adolescents Aged 12–19 Years: A Cross-Sectional Study - Gu, Fang; Luo, Xiaoming; Jin, Xiaoli; Cai, Changshou; Zhao, Wenyan (Frontiers in Medicine, 2022)
Aims: Evidence of a link between total calcium(CA) and serum uric acid(SUA) is absent in adolescents. Thus, this study aimed to determine the relationship between total CA levels and SUA levels in U.S. adolescents. Methods: A cross-sectional study analyzed a sample composed of 8309 U.S. adolescents aged 12–19 years from the National Health and Nutrition Examination Survey (NHANES) database (1999–2006 survey cycle). Multivariable linear regression analyses and multivariable logistic regression analyses were used to assess the correlation of total CA with SUA levels and hyperuricemia. Furthermore, the dose-response relationship of total CA and SUA levels was analyzed using smooth curve fitting (penalized spline method). Results: According to multivariable linear regression analysis, every 1 mg/dL increase in total CA level is associated with a 0.33 mg/dL (β = 0.33, 95% CI: 0.27−0.40, p <0.001) increase in SUA. Multivariable logistic regression analyses showed that every 0.1 mg/dL increase in total CA level is linked with an 8% increased risk of hyperuricemia (OR=1.08, 95% CI: 1.06−1.10, p <0.001). The analyses of smooth curve fitting revealed that total CA levels were linearly correlated with SUA levels (Pnonlinearity = 0.152). The results were highly stable in all subgroups. The interaction analysis results presented that race/ethnicity had an interactive role in associating total CA with SUA levels. Conclusions: In U.S. adolescents, total CA levels were linearly and positively correlated with SUA levels.